Concordance analysis between different methodologies used for identification of oral isolates of Candida species (2018)
Background: The yeasts species determination is fundamental not only for an accurate diagnosis but also for establishing a suitable patient treatment. We performed a concordance study of five methodologies for the species identification of oral isolates of Candida in Colombia. Methods: Sixty-seven Candida isolates were tested by; API® 20C-AUX, Vitek®2 Compact, Vitek®MS, Microflex® and a molecular test (panfungal PCR and sequencing). The commercial cost and processing time of the samples was done by graphical analysis. Results: Panfungal PCR differentiated 12 species of Candida, Vitek®MS and Microflex® methods identified 9 species, and API® 20C-AUX and Vitek®2 Compact methods identified 8 species each. Weighted Kappa (wK) showed a high agreement between Panfungal PCR, Vitek®MS, Microflex® and API® 20C-AUX (wK 0.62-0.93). The wK that involved the Vitek®2 Compact method presented moderate or good concordances compared with the other methods (wK 0.56-0.73). Methodologies based on MALDI TOF MS required 4 minutes to generate results and the Microflex® method had the lowest selling price. Conclusion: The methods evaluated showed high concordance in their results, being higher for the molecular methods and the methodologies based on MALDI TOF. The latter are faster and cheaper, presenting as promising alternatives for the routine identification of yeast species of the genus Candida. © 2018. Universidad del Valle.